The relationship between inertial measurement unit-derived 'force signatures' and ground reaction forces during cricket pace bowling. Issue 3 (3rd May 2020) - Callaghan, Samuel J.; Lockie, Robert G.; Andrews, Warren A.; Chipchase, Robert F.; Nimphius, Sophia
Abstract: This study assessed the reliability and validity of segment measured accelerations in comparison to front foot contact (FFC) ground reaction force (GRF) during the delivery stride for cricket pace bowlers. Eleven recreational bowlers completed a 30-delivery bowling spell. Trunk- and tibia-mounted inertial measurement units (IMUs) were used to measure accelerations, converted to force, for comparisons to force plate GRF discrete measures. These measures included peak force, impulse and the continuous force–time curve in the vertical and braking (horizontal) planes. Reliability and validity was determined by intra-class correlation coefficients (ICC), coefficient of variation (CV), Bland–Altman plots, paired sample t -tests, Pearson's correlation and one-dimensional (1D) statistical parametrical mapping (SPM). All ICC (0.90–0.98) and CV (4.23–7.41%) were acceptable, except for tibia-mounted IMU braking peak force (CV = 12.44%) and impulse (CV = 18.17%) and trunk vertical impulse (CV = 17.93%). Bland–Altman plots revealed wide limits of agreement between discrete IMU force signatures and force plate GRF. The 1D SPM outlined numerous significant ( p < 0.01) differences between trunk- and tibia-located IMU-derived measures and force plate GRF traces in vertical and braking (horizontal) planes. The trunk- and tibia-mounted IMUs appeared to not represent the GRF experienced during pace bowling FFC when compared to a gold-standard force plate.